Caspase-8 promotes scramblase-mediated phosphatidylserine exposure and fusion of osteoclast precursors - Krishnacoumar, Brenda; Stenzel, Martin; Garibagaoglu, Hilal; Omata, Yasunori; Sworn, Rachel L.; Hofmann, Thea; Ipseiz, Natacha; Czubala, Magdalena A.; Steffen, Ulrike; Maccataio, Antonio; Stoll, Cornelia; Böhm, Christina; et al. (Bone Research, 2024)
Efficient cellular fusion of mononuclear precursors is the prerequisite for the generation of fully functional multinucleated bone-resorbing osteoclasts. However, the exact molecular factors and mechanisms controlling osteoclast fusion remain incompletely understood. Here we identify RANKL-mediated activation of caspase-8 as early key event during osteoclast fusion. Single cell RNA sequencing-based analyses suggested that activation of parts of the apoptotic machinery accompanied the differentiation of osteoclast precursors into mature multinucleated osteoclasts. A subsequent characterization of osteoclast precursors confirmed that RANKL-mediated activation of caspase-8 promoted the non-apoptotic cleavage and activation of downstream effector caspases that translocated to the plasma membrane where they triggered activation of the phospholipid scramblase Xkr8. Xkr8-mediated exposure of phosphatidylserine, in turn, aided cellular fusion of osteoclast precursors and thereby allowed generation of functional multinucleated osteoclast syncytia and initiation of bone resorption. Pharmacological blockage or genetic deletion of caspase-8 accordingly interfered with fusion of osteoclasts and bone resorption resulting in increased bone mass in mice carrying a conditional deletion of caspase-8 in mononuclear osteoclast precursors. These data identify a novel pathway controlling osteoclast biology and bone turnover with the potential to serve as target for therapeutic intervention during diseases characterized by pathologic osteoclast-mediated bone loss. (Figure presented.)
CRIS-Team Scopus Importer:2024-07-19

IgA Complexes Induce Neutrophil Extracellular Trap Formation More Potently Than IgG Complexes - Gimpel, Anna; Maccataio, Antonio; Unterweger, Harald; Sokolova, Maria; Schett, Georg; Steffen, Ulrike (Frontiers in Immunology, 2022)
Neutrophil extracellular trap (NET) formation is a powerful instrument to fight pathogens, but may induce collateral damage in the affected tissues. Besides pathogen-derived factors, immune complexes are potent inducers of NET formation. Neutrophils express IgA and IgG specific Fc receptors (FcRs) and therefore respond to complexed IgA and IgG. Especially in the context of autoimmune diseases, IgA and IgG immune complexes have been shown to trigger NET formation, a process that putatively contributes to disease severity. However, it is of question if both antibody classes stimulate neutrophils to the same extent. In this study, we compared the capability of IgA and IgG complexes formed by heat aggregation to induce NET formation. While stimulation of neutrophils with IgA complexes robustly induced NET formation, complexed IgG only marginally increased the amount of NETs compared to the unstimulated control. Mixing IgA with IgG before heat aggregation did not increase the effect of complexed IgA on neutrophils. By contrast, the presence of IgG complexes seemed to disturb neutrophil stimulation by IgA complexes. The capacity of complexed IgG to induce NET formation could not be increased by the addition of autologous serum or the removal of terminal sialic acid in the Fc glycan. Together, our data show that IgA is a much more potent inducer of NET formation than IgG. IgA may thus be the main driving force in (auto)immune complex-mediated NET formation.
CRIS-Team Scopus Importer:2022-02-11
Keywords: IgA; IgG; immune complex; NET; neutrophil